Desenvolvimento e avaliação da atividade antifúngica de microesferas contendo extratos de Spondias purpurea frente a cepas de Candida spp - Coutinho, Tatiana do Nascimento Paiva (2024)
Fungal infections have increased on a global scale, leading to serious infections that affect more than 300 million people. It is believed that this expansion may be linked to factors such as environmental and socioeconomic changes, health care, antifungal resistance and emerging species. The current problem of increasing resistance of Candida spp. to available antifungals, has made the search for therapeutic options necessary and has led researchers to look for bioactives in nature with antimicrobial potential, as nature offers an arsenal of biomolecules. Therefore, the aim of this work was to develop microspheres based on galactomannan from Caesalpinia ferrea with extracts from Spondias purpurea and evaluate their effectiveness against Candida spp. biofilm and planktonic cells. The extracts were characterized by HPLCDAD and the microspheres were prepared by the spray drying technique and analyzes were carried out by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) to characterize the microspheres, in addition to the encapsulation efficiency by HPLC to quantify the extract in the microsphere. In microbiological analyses, broth microdiluition tests were carried out to determine the minimum inhibitory concentration and antibiofilme. Cytotoxicity and toxicity tests were also carried out. The microspheres had an average size of 5.81±2.35 µm and the MGC-1 encapsulation efficiency was 43%. The results of the MIC for the stem bark extracts (ECC-1 and ECC-2) were between 0.25 - 2 µg/mL, and the galactomannan microspheres (MGC-1 and MGC-2) between 1 - 8 µg/mL. In the biofilm in formation, the MGC-1 and MGC2 microspheres compared to the isolated extract showed a statistically significant improvement at 8xMIC (32 µg/mL) exhibiting 31% viability and 4xMIC (16 µg/mL) exhibiting 30% viability, respectively, for C. albicans 1, while for C. auris, it was at 4xMIC (16 µg/mL) showing 70% viabilit and 8xMIC (32 µg/mL) showing 60% viabilit, referring to the MGC-1 microsphere, and MIC/2 (2 µg/mL), 4xMIC (16 µg/mL), 8xMIC (32 µg/mL) and 12xMIC (48 µg/mL), showing 85,4%, 13%, 5% and 7% of viability, respectively for MGC-2. Furthermore, the extracts, galactomannan and microspheres did not show toxicity. This study revealed that the synthesized microspheres have the potential to be used as an antifungal agent.